INFLUENCE OF BUDGETARY PARTICIPATION, PERFORMANCE-BASED BUDGETING AND INTERNAL CONTROL SYSTEMS ON ORGANIZATIONAL PERFORMANCE - Denny Putri Gizelia; Suhairi Suhairi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
Research objective - The aim of the research is to examine the effect of budgetary participation, performance-based budgeting and internal control systems on organizational performance in the Sijunjung District Government Regional Apparatus Organization . Design/Methodology/Approach - The population of this research is all structural officials consisting of echelon III and echelon IV in 35 regional apparatus organizations in Sijunjung Regency totaling 310 respondents. A sample of 175 respondents was taken through a purposive sampling technique. The method of data analysis uses quantitative data analysis of structural equation models, namely Structural Equation Modeling - PLS-based SEM.  Findings - Budget participation has a positive and significant effect on organizational performance in the Regional Apparatus Organization of the Sijunjung Regency Government, performance-based budgeting has a positive and significant effect on organizational performance in the Sijunjung Regency Government Regional Government Organization, and the internal control system has a positive and significant effect on organizational performance in the Organization Sijunjung Regency Government Regional Apparatus. Research limitations – This research was conducted only at the Regional Ranking Organizations with the coverage of locations in Sijunjung Regency, so the results of this study cannot be generalized to the wider population. Originality – The research focus lies on the influence of budgetary participation, performance-based budgeting and internal control systems on organizational performance